INNOVATION IN PROCESSING INORGANIC ORGANIC WASTE IN CIBENDA VILLAGE PARIGI DISTRICT PANGANDARAN DISTRICT - Syahril, Syahril; Simbara, Adam; Boy, Gasper; Arifhan, Rafly Fadhilah; Margana, Riki Ridwan (Institut Teknologi Adhi Tama Surabaya, 2025)
Waste management is a significant challenge faced by many regions, including Desa Cibenda. Population growth, urbanization, and changing consumption patterns, waste management issues have become increasingly complex. This study aims to analyze waste management in Desa Cibenda, identify key challenges, and propose sustainable solutions. Several challenges were identified, including the lack of adequate waste disposal facilities. Inefficient management methods such as burning, low public awareness regarding waste separation, and economic limitations hindering investment in waste management. As a result, a large amount of waste is disposed of improperly, polluting the environment and reducing recycling potential. Desa Cibenda covers an area of 759.319 hectares, with a population of 8,229 people in 3,028 households, generating an average waste volume of 1.67 kg/person/day. Waste composition data from segregation showed 150 kg/day. Measurements were conducted using the load count analysis method, with three-wheeled vehicles that have a capacity of 200 kg/m³ used for waste transportation. This study recommends the procurement of a waste shredder to enhance the efficiency of organic and inorganic waste management. Other recommendations include providing adequate waste management facilities, educating the community on waste separation, and adopting community-based approaches to raise awareness and establish sustainable waste management practices.